Case report of a geminated premolar and hypodontia. (1st January 2020) - Sinnott, Paula; Sah, Sunil; Barker, Chris
Abstract : This case report describes the diagnosis and treatment of a non-syndromic unilateral geminated second premolar complicated by hypodontia of three second premolars. Gemination is defined as a developmental disturbance of the shape of teeth and is usually recognized as a partial cleavage of a single tooth germ resulting in one root and one pulp space with two partially or totally separated crowns. Hypodontia is defined as the developmental absence of one or more teeth, excluding the third molars. Geminations of maxillary second premolars are rarely reported. These dental anomalies can cause local malocclusion manifesting as crowding or spacing. CPD/Clinical Relevance: Diagnosis of dental anomalies such as gemination can be difficult. This paper discusses the diagnosis and management of one such case which involved CBCT.